2018
DOI: 10.1038/s41598-017-19138-4
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNA signature for the diagnosis of childhood dilated cardiomyopathy

Abstract: Circulating miRNAs are proposed as a biomarker of heart disease. This study evaluated whether circulating miRNAs could be used as a biomarker for childhood dilated cardiomyopathy (CDCM). A total of 28 participants were enrolled in a discovery set, including patients with CDCM (n = 16) and healthy children (n = 12). The cardiac function of patients with CDCM was characterized by echocardiography and serum miRNA profiles of all participants were assessed by miRNA sequencing. After miRNA profiling, we quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 28 publications
3
33
0
Order By: Relevance
“…Platelet extracellular vesicles exhibit upregulated miR-142-5p, which is involved in vascular and metabolic disease [21]. miR-142 is suppressed in a hypertrophic heart model and human cardiomyopathic hearts [22]. miR-142-5p was upregulated in heart failure patients undergoing implantation of a left ventricular assisting device.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet extracellular vesicles exhibit upregulated miR-142-5p, which is involved in vascular and metabolic disease [21]. miR-142 is suppressed in a hypertrophic heart model and human cardiomyopathic hearts [22]. miR-142-5p was upregulated in heart failure patients undergoing implantation of a left ventricular assisting device.…”
Section: Discussionmentioning
confidence: 99%
“…The circulating profile of miR-27b-3p, miR-126-3p, miR-142-5p, and miR-143-3p seems to discriminate between patients with DCM from healthy subjects. 66 Interestingly, Miyamoto et al 67 identified specific serum miR-NAs that can be used for risk stratification in children with DCM. Using an array for 754 miRNAs and RT-qPCR validation, the authors found a differential expression profile of miR-155, miR-636, miR-639, and miR-646 in patients who were transplanted or died compared with patients who recovered their ventricular function.…”
Section: Micrornas and Dilated Cardiomyopathymentioning
confidence: 99%
“…The cardiac function of patients with childhood dilated cardiomyopathy (CDCM) was characterized by echocardiography and serum miRNA profiles of all participants were assessed by miRNA sequencing. As a result, a unique signature comprising mir-142-5p, mir-143-3p, mir-27b-3p, and mir-126-3p differentiated patients with CDCM from healthy subjects [5]. Thus, circulating microRNAs (C-miRNAs) have emerged as measurable biomarkers (liquid biopsies) for not only various cancer detection but other diseases.…”
Section: Editorialmentioning
confidence: 99%